A Preliminary Study of Ocimum basilicum Essential Oil as a Repellent against Aedes aegypti in Surabaya - Wahyuni, Afrinda Dwi; Zahra, Siti Fatimatuz; Putri, Balqis Qonita; Pramudya, Manikya; Rohmah, Etik Ainun; Mulyatno, Kris Cahyo (Journal of Public Health for Tropical and Coastal Region, 2022)
Introduction: Aedes aegypti is the main dengue vector in Indonesia. One of the dengue controls is through insecticides use. The plant-based insecticide is one alternative that can be used to minimize the impact of chemical insecticides. Ocimum basilicum is one of the plants that have the potency to be used as insecticides. The aims of this study were to analyze the insecticide activity of Ocimum basilicum essential oil against Aedes aegypti as well as its Lethal Concentration (LC50 and LC90) and Knockdown Time ( KT50 and KT90).Methods: Treatment groups were given Ocimum basilicum essential oil of 100 ppm, 50 ppm, and 25 ppm. The tests were performed four times with 10 mosquitoes per test.Results: The mortality rate of the mosquito on the extract with a concentration of 100 ppm was 100%, 50 ppm was 10% and 25 ppm was 0% and the value of LC50 = 62.9 ppm and LC90 = 78.7 ppm. KT50 of this study was 19.4 minutes and KT90 was 8.07 minutes.Conclusion: Ocimum basilicum essential oil has a mosquitocidal effect on Aedes aegypti. Further studies to investigate the substances of Ocimum basilicum against Aedes aegypti are needed.